2002
DOI: 10.1080/03014223.2002.9517713
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene extinction of Finsch's duck(Chenonetta finschi),an endemic, possibly flightless, New Zealand duck

Abstract: Finsch's duck (Chenonetta finschi), an extinct, possibly flightless New Zealand endemic, was widely distributed and apparently abundant immediately before human settlement of New Zealand, but its bones have rarely been identified in archaeological sites. Its extinction has been variously attributed to habitat changes, predation by the introduced Pacific rat (Rattus exulans), and human predation. Discriminating between possible causes of its extinction hinges on determining the relative timing of phases of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…use of open vs. sub-canopy habitats) are the two most likely factors differentiating the δ 13 C values of these species at Finsch's folly tomo. Holdaway et al (2002) and Worthy and Holdaway (2002) also reported relatively depleted 13 C values for Finsch's duck, the latter authors suggesting this result reflected feeding beneath a dense canopy. However, it can be difficult to attribute any one factor to explaining δ 13 C values (Dawson et al 2002).…”
Section: Trophic Positionsmentioning
confidence: 90%
“…use of open vs. sub-canopy habitats) are the two most likely factors differentiating the δ 13 C values of these species at Finsch's folly tomo. Holdaway et al (2002) and Worthy and Holdaway (2002) also reported relatively depleted 13 C values for Finsch's duck, the latter authors suggesting this result reflected feeding beneath a dense canopy. However, it can be difficult to attribute any one factor to explaining δ 13 C values (Dawson et al 2002).…”
Section: Trophic Positionsmentioning
confidence: 90%
“…If a site contained the remains of taxa introduced by Europeans and the remains of extinct taxa, it was assumed that the record in that site was continuous through the period of interest. Holdaway et al (2002). AMS 14 C dates are reported as conventional radiocarbon ages (CRA, years BP) as defined by Stuiver & Polach (1977), and as calibrated dates.…”
Section: Late Holocene Distributionmentioning
confidence: 99%
“…Using 12 of the 20 determinations on A. novaezealandiae bone, we sought to establish the time range over which the extinction of this species occurred using the Bayesian model presented by Holdaway et al (2002) to examine the extinction of Finsch's duck (Chenonetta finschi). Briefly, assuming that the dated capture events (an owlet-nightjar caught by a laughing owl) can be described as a constant rate Poisson process (this describes discrete random temporal events of relatively low temporal frequency), we can compute posterior distributions for parameters of interest via sample-based Bayesian inference.…”
Section: Statistical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These distributions can then be compared with others for the establishment of predators or other potential factors in the extinction. Such probability distributions are available at present for only two species, Finsch's duck (Holdaway et al 2002a) and the New Zealand owlet-nightjar (Holdaway et al 2002b). Those analyses suggest that both species may have started their declines towards extinction before the most recent estimates for initial Polynesian settlement of AD 1280-1300 (Higham et al 1999;Lowe et al 2000).…”
Section: Introductionmentioning
confidence: 99%